Program SESAMA: Edukasi Hidup Sehat dengan Tanaman Sehat untuk Pengendalian Hipertensi di Desa Pondok: Pengabdian - Dinda Dwi Ariani; Triska Susila Nindya; R. Azizah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Healthy Living with Healthy Plants (SESAMA) Socialization and Education Program was implemented in Pondok Village, Ponorogo Regency, as a community-based hypertension control effort. The objective of this activity was to increase public knowledge and awareness about hypertension and encourage the adoption of a healthy lifestyle through the use of local plants, especially cucumbers, which have the potential to lower blood pressure naturally. The implementation method was carried out on January 23, 2025, involving 47 participants aged 45–75 years through a pre-test stage, presentation of material on hypertension and healthy plants, cucumber planting practice, interactive discussion, and a post-test as an evaluation. The approach used not only focused on delivering information, but also practical skills so that the community was able to apply the knowledge gained in everyday life. The results of the activity showed a significant increase in participant knowledge, with an average pre-test score of 44,40 and a post-test increase to 75,30%, or an increase of 30,9%. These findings prove that health education combined with direct practice can be an effective strategy in preventing hypertension. In addition to providing health benefits, this activity also fosters community independence in utilizing local plants sustainably. Thus, the SESAMA program has the potential to become a simple, economical, and applicable intervention model in controlling hypertension at the village level.